Dry skin and the use of leave‐on products in nursing care: A prevalence study in nursing homes and hospitals. Issue 1 (27th September 2018) - Lechner, Anna; Lahmann, Nils; Lichterfeld‐Kottner, Andrea; Müller‐Werdan, Ursula; Blume‐Peytavi, Ulrike; Kottner, Jan
Abstract: Aims: To describe the prevalence of dry skin in nursing homes and hospitals and to describe relationships between topical skincare interventions and dry skin. Design: Two multicentre descriptive cross‐sectional prevalence studies. Methods: The studies were performed in German nursing homes and hospitals in 2015 and 2016. Data were collected by trained nurses based on a standardized data collection form. The severity of dry skin was measured using the Overall Dry Skin Score. Results: In total, 1, 662 nursing home residents and 1, 486 hospital patients participated. The prevalence of dry skin was 41.2% in nursing homes and 55.2% in hospitals. In case of skincare dependency, the proportions of participants with dry skin were higher, particularly in hospitals (70.2%). In both institutions, the application of leave‐on products increased when dry skin was present but remained lower in hospitals. Considering the high amount of skin dryness in skincare‐dependent participants, interventions seem not to be successful. Results indicate a need for skincare improvement in future.